Preparation method and application of renewable hydrogenation catalyst
By using SiO2-TiO2 composite support and palladium-rhodium active components in the nitrobenzene hydrogenation catalyst, and through additives and phosphating treatment, a renewable hydrogenation catalyst was prepared, which solved the problems of noble metal agglomeration and loss, low reaction selectivity and low catalyst reuse efficiency, and achieved efficient catalyst regeneration and long life catalytic effects.
Patent Information
- Application Number
- CN202510003117.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-15
AI Technical Summary
The existing nitrobenzene hydrogenation catalysts have problems such as noble metal agglomeration and loss, low reaction selectivity and low catalyst reuse efficiency.
A renewable hydrogenation catalyst was prepared by using SiO2-TiO2 complex as the support and palladium-rhodium as the active component. This catalyst improves stability and reactivity by controlling the degree of phosphating of the additive and the ratio of the catalyst, thereby realizing the active regeneration of the catalyst.
It effectively reduces the amount of impurities, improves the selectivity of aniline, reduces the agglomeration and loss of precious metals, and restores the catalyst activity from 50% to 99% through secondary phosphation, extending the service life of the catalyst.
Smart Images

Figure BDA0005226026290000091
Abstract
Description
Technical Field
[0001] The invention belongs to the field of hydrogenation catalysts, and in particular relates to a preparation method and application of a regenerable hydrogenation catalyst. Background Art
[0002] Aniline, as an important organic intermediate, is widely discontinued in rubber, pesticide, dye and other industries. At present, the mainstream process is nitrobenzene liquid phase catalytic hydrogenation. The catalyst of the hydrogenation process involves precious metals. Since the industrial device uses the heat of the hydrogenation reaction and controls the reaction temperature above 200°C, the loss or agglomeration of the precious metal components is caused, which greatly reduces the activity and requires continuous addition of fresh catalyst to ensure the reaction activity. For example, CN115155575B synthesized a diatomic supported catalyst and applied it to nitrobenzene hydrogenation catalysis. The catalyst uses a single-atom type precious metal, which greatly improves the atomic utilization rate and has a small amount of precious metal loading, but there is a problem of precious metal agglomeration under high temperature environment. CN 114632512 A invented a nitrobenzene hydrogenation catalyst composed of platinum, metal additives, silica carriers and a silica mesh structure coated with active metals. The special mesh structure can effectively inhibit the loss or agglomeration of active components, but its by-products are more and the aniline yield is low. At the same time, in the industrial production process, the catalyst is constantly broken during operation, forming small particles, which flow out of the system with aniline and are then enriched in tar to recover precious metals through incineration. In the process, a large amount of precious metals are lost, leading to rising costs. Currently, the main research focuses on how to improve the recovery rate of precious metals, but there is still room for improvement in efficiency.
[0003] In summary, there are still urgent problems to be solved for nitrobenzene hydrogenation catalysts, such as reducing active metal agglomeration and loss, improving reaction selectivity, and reusing deactivated catalysts. Summary of the invention
[0004] The present invention is based on the deficiencies of the existing nitrobenzene hydrogenation catalyst technology and provides a regenerable hydrogenation catalyst. The catalyst greatly reduces the amount of impurities generated during the hydrogenation process, and in particular, can effectively inhibit the generation of key impurities aminodiphenylamine and aminophenol, has extremely high aniline selectivity, and the active components are not easy to agglomerate and lose. At the same time, the catalyst activity can be regenerated through secondary phosphating, and has a good prospect for industrial application.
[0005] In order to achieve the above invention object, the present invention is implemented by the following technical solutions:
[0006] A regenerable hydrogenation catalyst, the catalyst uses a SiO2-TiO2 composite as a carrier, palladium and rhodium as active components, and an additive is added, and the catalyst composition is as follows:
[0007] PdRh-M / MP(m)-SiO2 / TiO2(n)
[0008] Wherein, the content of loaded palladium is 1-5wt%, and the content of loaded rhodium is 0.5-3wt%;
[0009] Wherein, M is a catalyst additive, MP is an additive phosphide, and the content of the two additives is 1-10wt%;
[0010] Wherein, MP partially phosphatizes M, and preferably the molar ratio m of the auxiliary agent M to MP is 5-20.
[0011] The inventors have found that in the synthesis of catalysts, the degree of phosphating of the auxiliary metal is controlled so that part of the auxiliary metal forms a phosphide shell to protect the catalyst sites from being etched by acidic byproducts, thereby improving the stability of the catalyst. At the same time, the phosphide can adjust the electronic structure to enhance the reaction activity of the active sites of the precious metals and change the acidity and alkalinity of the catalyst surface to adjust the selectivity of the reaction.
[0012] Another object of the present invention is to provide a method for preparing the catalyst.
[0013] A method for preparing the above catalyst, the method comprising the following steps:
[0014] S1: A mixed solution of silicon source and titanium source is prepared and then aged, washed, dried and calcined to obtain a SiO2-TiO2 composite carrier;
[0015] S2: Grind the carrier into powder, add the precursor salt solution of M, mix, and dry to obtain the intermediate A with added M;
[0016] S3: Partially phosphating the intermediate A to obtain the intermediate B;
[0017] S4: Grind the intermediate B into powder, add solutions of palladium salt and rhodium salt, mix, dry and reduce to obtain the target catalyst;
[0018] Optionally, S5: the used catalyst is dried and partially phosphated again to obtain a regenerated catalyst.
[0019] In one embodiment of the present invention, the silicon source in S1 comprises a silicate compound, preferably one or more of ethyl orthosilicate, methyl orthosilicate, and tetrabutyl silicate.
[0020] In one embodiment of the present invention, the titanium source in S1 comprises alkyl titanate, preferably tetrabutyl titanate and / or tetrapropyl titanate; preferably, the molar ratio n of silicon and titanium atoms is 8-15; preferably, the m / n ratio is 2:1-1:2.
[0021] In one embodiment of the present invention, a surfactant is added to S1, preferably the surfactant is a non-ionic surfactant, more preferably one or more of F127, F108 and P123.
[0022] In one embodiment of the present invention, an acid is added to S1, preferably the acid is an inorganic acid, more preferably hydrochloric acid; preferably, the mass ratio of the surfactant to the acid is 1:(1.2-1.8);
[0023] In the present invention, the temperature of the mixed solution prepared in S1 is 30-80°C.
[0024] In one embodiment of the present invention, the aging treatment time in S1 is 24-72 hours and the temperature is 150-220°C.
[0025] In one embodiment of the present invention, the calcination temperature in S1 is 400-650° C. and the time is 4-8 hours.
[0026] In one embodiment of the present invention, the precursor salt of M of S2 comprises a soluble salt of one or more of Fe, Co, Zn, and Ni, preferably one or more of iron nitrate, cobalt nitrate, zinc nitrate, and nickel nitrate.
[0027] In one embodiment of the present invention, the phosphating agent used in the S3 phosphating treatment comprises an inorganic phosphate, preferably one or more of sodium phosphate, sodium hydrogen phosphate, and sodium dihydrogen phosphate.
[0028] In one embodiment of the present invention, the phosphating temperature in S3 is 200-500° C. and the time is 1-3 hours.
[0029] In one embodiment of the present invention, the palladium salt in S4 comprises one or more of chloroplatinic acid, platinum nitrate, platinum tetrachloride, and potassium chloroplatinate.
[0030] In one embodiment of the present invention, the rhodium salt in S4 comprises rhodium nitrate and / or rhodium trichloride.
[0031] In one embodiment of the present invention, S4 is reduced to a hydrogen atmosphere at a temperature of 200-400° C. for 2-4 h.
[0032] In one embodiment of the present invention, the phosphating method in S5 is the same as that in S3.
[0033] Another object of the present invention is to provide a use of a regenerable hydrogenation catalyst.
[0034] A use of a regenerable hydrogenation catalyst, wherein the catalyst is the above catalyst, or a catalyst prepared by the above method, and the catalyst is used for hydrogenation reaction, preferably for nitrobenzene hydrogenation.
[0035] Another object of the present invention is to provide a method for hydrogenating nitrobenzene using a regenerable hydrogenation catalyst.
[0036] A method for hydrogenating nitrobenzene using a renewable hydrogenation catalyst, the method using the above catalyst, or a catalyst prepared by the above method, in which the reaction temperature is 80-200°C, the reaction pressure is 0.5-2MPaG, and the molar ratio of hydrogen to nitrobenzene is (3-3.5):1.
[0037] Compared with the prior art, the present invention has the following advantages:
[0038] (1) By treating the carrier and the additive to obtain a partially phosphated catalyst, the aggregation and loss of active metals can be effectively reduced and the catalyst stability can be improved.
[0039] (2) By controlling the catalyst phosphating ratio and silicon-titanium ratio and adjusting the acid-base properties of the catalyst surface, the content of key impurities aminodiphenylamine and aminophenol can be reduced and the selectivity of aniline can be improved.
[0040] (3) By rephosphating the deactivated catalyst, the activity of the precious metal sites can be enhanced again, and the catalyst activity can be restored from 50% to 99%, thereby extending the service life of the catalyst.
[0041] The catalyst prepared by the present invention is a nitrobenzene hydrogenation catalyst. Due to the special design of the catalyst, it can still ensure a very high conversion rate under a low noble metal loading. In addition, the catalyst preparation process is simple, the required raw materials are low in cost and easy to obtain, and it has good stability and high industrial application value. DETAILED DESCRIPTION
[0042] The present invention is described in more detail below in conjunction with the embodiments, but it should be noted that the following embodiments are not limiting examples of the scope of the present invention.
[0043] In order to more clearly illustrate the present invention, the following examples are given, but they do not limit the scope of the present invention in any way.
[0044] Raw materials: All chemicals were purchased from Inokai, F127: average molecular weight 10,000; P123: average molecular weight 5,800; hydrochloric acid: concentration 37%; tetraethyl orthosilicate: 99%; tetrabutyl silicate: 99%; tetrabutyl titanate: 99%; tetrapropyl titanate: 99%; sodium dihydrogen phosphate: 99%; sodium hydrogen phosphate: 99%; palladium dichloride: 98%; palladium nitrate: 98%; rhodium trichloride: 98%; rhodium nitrate: 98%; ferric nitrate: 98%; cobalt nitrate: 98%;.
[0045] Gas chromatography analysis conditions: Agilent 7890B, chromatographic column: HP-5 (30m x 530μm x 1.5μm), automatic sampler, injection port temperature: 280℃, septum purge flow: 3ml / min, split ratio 10:1, injection volume: 0.8ul, programmed temperature: 50℃ for 1min, increase the temperature to 150℃ at 5℃ / min, maintain for 2min, increase the temperature to 160℃ at 10℃ / min, maintain for 1min, increase the temperature to 200℃ at 15℃ / min, maintain for 0min, increase the temperature to 280℃ at 20℃ / min, maintain for 5min, detector: 280℃, hydrogen flow: 40mL / min, air flow: 400mL / min, tail gas flow: 25mL / min.
[0046] The present invention adopts a kettle reactor to evaluate the performance of the catalyst. 0.7g of dry catalyst, 144g of aniline and 22g of water are added into the reactor as the reaction bottom liquid. Nitrobenzene is fed at 2.2ml / min, hydrogen is fed at 1.34-1.57NL / min, the reaction temperature is maintained at 80-200°C, the pressure is 0.5-2Mpa(g), the stirring rate is 1000rpm, the material is continuously fed and discharged, and the gas phase is sampled after the reaction is stable for 2h to analyze the content of each component in the product by chromatography.
[0047] Example 1
[0048] Preparation of PdRh-Fe / Fe3P(10)-SiO2 / TiO2(8) catalyst and activity testing.
[0049] Step 1: Weigh 2.5g F127 surfactant and dissolve it in 85ml deionized water, then add 10.27ml 10mol / L hydrochloric acid solution, stir at room temperature for 1h to fully dissolve; after dissolution, measure 8ml of ethyl orthosilicate and add it to the above mixed solution, place it in an oil bath at 40℃ and magnetically stir it for 6h; then measure 1ml tetrabutyl titanate in the solution, stir it in an oil bath at 80℃ for 20h, then transfer the mixed solution to a hydrothermal kettle and keep it at 180℃ for 24h. After taking out the hydrothermal kettle and cooling it, the hydrothermal reaction liquid is filtered and washed, and washed with ethanol and pure water three times to pH 7 respectively. The washed solid is dried in an oven at 120℃ for 12h, and then placed in a muffle furnace and calcined at 450℃ (heating rate 2℃ / min) for 4h to obtain a silicon aluminum oxide carrier.
[0050] Step 2: Grind 3 g of the solid obtained in step 1 into powder, add 3.75 ml of 0.5 mol / L ferric nitrate solution, stir for 6 hours to obtain a slurry, dry it at 120°C for 12 hours, then place it in a tube furnace, add 0.165 g of sodium dihydrogen phosphate, phosphating for 2 hours at a phosphating temperature of 300°C to obtain a phosphated catalyst.
[0051] Step 3: Grind 2.5 g of the solid obtained in step 1 into powder, add 4.7 ml of the prepared 0.1 mol / L palladium dichloride and 1.3 ml of 0.1 mol / L rhodium trichloride solution in sequence, stir for 6 hours to obtain a slurry, and vacuum dry the obtained slurry at 65 ° C for 12 h. After drying, place the solid in a tubular furnace at 200 ° C (heating rate 2 ° C / min) in a hydrogen atmosphere for reduction for 2 h to obtain the target catalyst.
[0052] Step 4: Add 0.7g dry catalyst, 144g aniline and 22g water into the reactor as the reaction base liquid. Feed nitrobenzene at 2.2ml / min, hydrogen at 1.4NL / min, maintain reaction temperature at 200°C, pressure at 1.7Mpa(g), stirring rate at 1000rpm, feed and discharge continuously, sample gas phase after the reaction is stable for 2h, and analyze the content of each component in the product by chromatographic analysis.
[0053] Example 2
[0054] Preparation and activity test of PdRh-Fe / Fe3P(10)-SiO2 / TiO2(15) catalyst.
[0055] Step 1: Weigh 2.5g F127 surfactant and dissolve it in 85ml deionized water, then add 10.27ml 10mol / L hydrochloric acid solution, stir at room temperature for 1h to fully dissolve; after dissolution, measure 15ml tetrabutyl silicate and add it to the above mixed solution, place it in an oil bath at 40℃ and magnetically stir it for 6h; then measure 1ml tetrabutyl titanate in the solution, stir it in an oil bath at 80℃ for 20h, then transfer the mixed solution to a hydrothermal kettle and keep it at 180℃ for 24h. After taking out the hydrothermal kettle and cooling it, the hydrothermal reaction liquid is filtered and washed, and washed with ethanol and pure water three times to pH 7 respectively. The washed solid is dried in an oven at 120℃ for 12h, and then placed in a muffle furnace and calcined at 450℃ (heating rate 2℃ / min) for 4h to obtain a silicon aluminum oxide carrier.
[0056] Step 2: Grind 3 g of the solid obtained in step 1 into powder, add 3.75 ml of 0.5 mol / L ferric nitrate solution, stir for 6 hours to obtain a slurry, dry it at 120°C for 12 hours, then place it in a tube furnace, add 0.165 g of sodium dihydrogen phosphate, phosphating for 3 hours at a phosphating temperature of 300°C to obtain a phosphated catalyst.
[0057] Step 3: Step 3: Take 2.5g of the solid obtained in step 1 and grind it into powder, add 4.7ml of the prepared 0.1mol / L palladium nitrate and 1.3ml of 0.1mol / L rhodium trichloride solution in sequence, stir for 6 hours to obtain a slurry, and vacuum dry the obtained slurry at 65°C for 12h. After drying, the solid is placed in a tubular furnace at 300°C (heating rate 2°C / min) in a hydrogen atmosphere for reduction for 2h to obtain the target catalyst.
[0058] Step 4: Add 0.7g dry catalyst, 144g aniline and 22g water into the reactor as the reaction base liquid. Feed nitrobenzene at 2.2ml / min, hydrogen at 1.55NL / min, maintain reaction temperature at 200°C, pressure at 1.7Mpa(g), stirring rate at 1000rpm, feed and discharge continuously, sample gas phase after the reaction is stable for 2h, and analyze the content of each component in the product by chromatographic analysis.
[0059] Example 3
[0060] Preparation and activity test of PdRh-Fe / Fe3P(20)-SiO2 / TiO2(8) catalyst.
[0061] Step 1: Weigh 2.5g F127 surfactant and dissolve it in 85ml deionized water, then add 10.27ml 10mol / L hydrochloric acid solution, stir at room temperature for 1h to fully dissolve; after dissolution, measure 8ml of tetraethyl orthosilicate and add it to the above mixed solution, place it in an oil bath at 40℃ and magnetically stir it for 6h; then measure 1ml tetrapropyl titanate in the solution, stir it in an oil bath at 80℃ for 20h, then transfer the mixed solution to a hydrothermal kettle and keep it at 180℃ for 24h. After taking out the hydrothermal kettle and cooling it, the hydrothermal reaction liquid is filtered and washed, and washed with ethanol and pure water three times to pH 7 respectively. The washed solid is dried in an oven at 120℃ for 12h, and then placed in a muffle furnace and calcined at 450℃ (heating rate 2℃ / min) for 4h to obtain a silicon aluminum oxide carrier.
[0062] Step 2: Grind 3 g of the solid obtained in step 1 into powder, add 7.5 ml of 0.5 mol / L ferric nitrate solution, stir for 6 hours to obtain a slurry, dry it at 120°C for 12 hours, then place it in a tube furnace, add 0.08 g of sodium dihydrogen phosphate, phosphate for 2 hours, and phosphate at 400°C to obtain a phosphated catalyst.
[0063] Step 3: Grind 2.5 g of the solid obtained in step 1 into powder, add 4.7 ml of the prepared 0.1 mol / L palladium dichloride and 1.3 ml of 0.1 mol / L rhodium nitrate solution in sequence, stir for 6 hours to obtain a slurry, and vacuum dry the obtained slurry at 65 ° C for 12 hours. After drying, place the solid in a tubular furnace at 200 ° C (heating rate 2 ° C / min) in a hydrogen atmosphere for reduction for 4 hours to obtain the target catalyst.
[0064] Step 4: Add 0.7g dry catalyst, 144g aniline and 22g water into the reactor as the reaction base liquid. Feed nitrobenzene at 2.2ml / min, hydrogen at 1.4NL / min, maintain reaction temperature at 200°C, pressure at 1.7Mpa(g), stirring rate at 1000rpm, feed and discharge continuously, sample gas phase after the reaction is stable for 2h, and analyze the content of each component in the product by chromatographic analysis.
[0065] Example 4
[0066] Preparation and activity test of PdRh-Co / Co2P(20)-SiO2 / TiO2(15) catalyst.
[0067] Step 1: Weigh 2.5g of P123 surfactant and dissolve it in 85ml of deionized water, then add 10.27ml of 10mol / L hydrochloric acid solution and stir at room temperature for 1h to fully dissolve; after dissolution, measure 15ml of ethyl orthosilicate and add it to the above mixed solution, place it in an oil bath at 40℃ and magnetically stir it for 6h; then measure 1ml of tetrabutyl titanate in the solution, stir it in an oil bath at 80℃ for 20h, then transfer the mixed solution to a hydrothermal kettle and keep it at 180℃ for 24h. After taking out the hydrothermal kettle and cooling it, filter and wash the hydrothermal reaction liquid, wash it with ethanol and pure water three times to pH 7, dry the washed solid in an oven at 120℃ for 12h, and then calcine it in a muffle furnace at 450℃ (heating rate 2℃ / min) for 4h to obtain a silicon aluminum oxide carrier.
[0068] Step 2: Grind 3 g of the solid obtained in step 1 into powder, add 3.75 ml of 0.5 mol / L cobalt nitrate solution, stir for 6 hours to obtain a slurry, dry it at 120° C. for 12 hours, then place it in a tube furnace, add 0.08 g of sodium dihydrogen phosphate, phosphate for 2 hours, and phosphate at 300° C. to obtain a phosphated catalyst.
[0069] Step 3: Grind 2.5 g of the solid obtained in step 1 into powder, add 4.7 ml of the prepared 0.1 mol / L palladium dichloride and 1.3 ml of 0.1 mol / L rhodium trichloride solution in sequence, stir for 6 hours to obtain a slurry, and vacuum dry the obtained slurry at 65 ° C for 12 h. After drying, place the solid in a tubular furnace at 200 ° C (heating rate 2 ° C / min) in a hydrogen atmosphere for reduction for 2 h to obtain the target catalyst.
[0070] Step 4: Add 0.7g dry catalyst, 144g aniline and 22g water into the reactor as the reaction base liquid. Feed nitrobenzene at 2.2ml / min, hydrogen at 1.4NL / min, maintain reaction temperature at 200°C, pressure at 1.7Mpa(g), stirring rate at 1000rpm, feed and discharge continuously, sample gas phase after the reaction is stable for 2h, and analyze the content of each component in the product by chromatographic analysis.
[0071] Example 5
[0072] Preparation and activity testing of PdRh-Fe / Fe3P(5)-SiO2 / TiO2(8) catalyst.
[0073] Step 1: Weigh 2.5g F127 surfactant and dissolve it in 85ml deionized water, then add 8.22ml 10mol / L hydrochloric acid solution, stir at room temperature for 1h to fully dissolve; after dissolution, measure 8ml of ethyl orthosilicate and add it to the above mixed solution, place it in an oil bath at 80℃ and magnetically stir it for 6h; then measure 1ml tetrabutyl titanate in the solution, stir it in an oil bath at 80℃ for 20h, then transfer the mixed solution to a hydrothermal kettle and keep it at 180℃ for 72h. After taking out the hydrothermal kettle and cooling it, the hydrothermal reaction liquid is filtered and washed, and washed with ethanol and pure water three times to pH 7 respectively. The washed solid is dried in an oven at 120℃ for 12h, and then placed in a muffle furnace and calcined at 450℃ (heating rate 2℃ / min) for 4h to obtain a silicon aluminum oxide carrier.
[0074] Step 2: Grind 3 g of the solid obtained in step 1 into powder, add 3.75 ml of 0.5 mol / L ferric nitrate solution, stir for 6 hours to obtain a slurry, dry it at 120°C for 12 hours, then place it in a tube furnace, add 0.33 g of sodium hydrogen phosphate, phosphating for 2 hours at a phosphating temperature of 300°C to obtain a phosphated catalyst.
[0075] Step 3: Grind 2.5 g of the solid obtained in step 1 into powder, add 1.6 ml of the prepared 0.1 mol / L palladium dichloride and 1.3 ml of 0.1 mol / L rhodium trichloride solution in sequence, stir for 6 hours to obtain a slurry, and vacuum dry the obtained slurry at 65 ° C for 12 h. After drying, place the solid in a tubular furnace at 200 ° C (heating rate 2 ° C / min) in a hydrogen atmosphere for reduction for 2 h to obtain the target catalyst.
[0076] Step 4: Add 0.7g dry catalyst, 144g aniline and 22g water into the reactor as the reaction base liquid. Feed nitrobenzene at 2.2ml / min, hydrogen at 1.4NL / min, maintain reaction temperature at 200°C, pressure at 0.8Mpa(g), stirring rate at 1000rpm, feed and discharge continuously, sample gas phase after the reaction is stable for 2h, and analyze the content of each component in the product by chromatographic analysis.
[0077] Example 6
[0078] Preparation and activity test of PdRh-Fe / Fe3P(5)-SiO2 / TiO2(15) catalyst.
[0079] Step 1: Weigh 2.5g F127 surfactant and dissolve it in 85ml deionized water, then add 10.27ml 10mol / L hydrochloric acid solution, stir at room temperature for 1h to fully dissolve; after dissolution, measure 15ml of ethyl orthosilicate and add it to the above mixed solution, place it in an oil bath at 40℃ and magnetically stir it for 6h; then measure 1ml tetrabutyl titanate in the solution, stir it in an oil bath at 80℃ for 20h, then transfer the mixed solution to a hydrothermal kettle and keep it at 180℃ for 24h. After taking out the hydrothermal kettle and cooling it, the hydrothermal reaction liquid is filtered and washed, and washed with ethanol and pure water three times to pH 7 respectively. The washed solid is dried in an oven at 120℃ for 12h, and then placed in a muffle furnace and calcined at 450℃ (heating rate 2℃ / min) for 4h to obtain a silicon aluminum oxide carrier.
[0080] Step 2: Grind 3 g of the solid obtained in step 1 into powder, add 3.75 ml of 0.5 mol / L ferric nitrate solution, stir for 6 hours to obtain a slurry, dry it at 120°C for 12 hours, then place it in a tube furnace, add 0.33 g of sodium dihydrogen phosphate, phosphate for 2 hours, and phosphate at 300°C to obtain a phosphated catalyst.
[0081] Step 3: Grind 2.5 g of the solid obtained in step 1 into powder, add 4.7 ml of the prepared 0.1 mol / L palladium dichloride and 0.3 ml of 0.1 mol / L rhodium trichloride solution in sequence, stir for 6 hours to obtain a slurry, and vacuum dry the obtained slurry at 65 ° C for 12 h. After drying, place the solid in a tubular furnace at 200 ° C (heating rate 2 ° C / min) in a hydrogen atmosphere for reduction for 2 h to obtain the target catalyst.
[0082] Step 4: Add 0.7g dry catalyst, 144g aniline and 22g water into the reactor as the reaction base liquid. Feed nitrobenzene at 2.2ml / min, hydrogen at 1.4NL / min, maintain the reaction temperature at 100°C, pressure at 1.7Mpa(g), stirring at 1000rpm, feed and discharge continuously, and sample the gas phase after the reaction is stable for 2h to analyze the content of each component in the product by chromatography.
[0083] Example 7
[0084] Preparation and activity test of PdRh-Fe / Fe3P(10)-SiO2 / TiO2(8) regenerated catalyst.
[0085] Step 1: Carry out a small-scale continuous hydrogenation experiment on the catalyst of Example 1, add 0.7g dry catalyst, 144g aniline and 22g water into the reactor as the reaction bottom liquid. Nitrobenzene feed 2.2ml / min, hydrogen feed 1.4NL / min, reaction temperature maintained at 200°C, pressure 1.7Mpa, stirring rate 1000rpm, continuous feeding and discharging, sample gas phase chromatographic analysis of each component content in the product every 2h after the reaction is stable, until the catalyst activity drops to 50% of the original catalyst, filter and dry the catalyst from the reaction liquid, then place it in a tubular furnace, add 0.165g sodium dihydrogen phosphate, phosphating time is 2h, phosphating temperature is 300°C, and obtain the regenerated catalyst.
[0086] Step 2: Add 0.7g dry catalyst, 144g aniline and 22g water into the reactor as the reaction base liquid. Feed nitrobenzene at 2.2ml / min, hydrogen at 1.4NL / min, maintain reaction temperature at 200°C, pressure at 1.7Mpa(g), stirring rate at 1000rpm, feed and discharge continuously, sample gas phase after the reaction is stable for 2h, and analyze the content of each component in the product by chromatographic analysis.
[0087] Comparative Example 1
[0088] Preparation of PdRh-Fe-SiO2 / TiO2(8) catalyst (without phosphating treatment)
[0089] Compared with Example 1, no phosphating treatment is performed in step 2. Other conditions are the same as in Example 1.
[0090] Comparative Example 2
[0091] Preparation of PdRh-Fe / Fe3P(1)-SiO2 / TiO2(8) Catalyst (High Phosphate Ratio)
[0092] Compared with Example 1, 1.65 g of sodium dihydrogen phosphate was added in step 2. Other conditions were the same as in Example 1.
[0093] Comparative Example 3
[0094] Pd-Fe / Fe3P(10)-SiO2 / TiO2(8)(without precious metal rhodium)
[0095] Compared with Example 1, the precious metal rhodium is not added in step 3. Other conditions are the same as in Example 1.
[0096] Comparative Example 4
[0097] Preparation of Rh-Fe / Fe3P(10)-SiO2 / TiO2(8) Catalyst (No Precious Metal Palladium)
[0098] Compared with Example 1, the precious metal palladium is not added in step 3. Other conditions are the same as in Example 1.
[0099] Comparative Example 5
[0100] Preparation of Deactivated PdRh-Fe / Fe3P(10)-SiO2 / TiO2(8) Catalyst
[0101] Compared with Example 7, sodium hypophosphite is not used for rephosphating. Other conditions are the same as those in Example.
[0102] By comparing the above examples with the comparative examples, it can be found that the solution of the present invention reduces the agglomeration and loss of active metals, improves the reaction selectivity and solves the problem of reusing the deactivated catalyst.
[0103] Table 1 Catalytic hydrogenation performance of examples
[0104]
[0105] Those skilled in the art will appreciate that, based on the teachings of this specification, some modifications or adjustments may be made to the present invention, and these modifications or adjustments should also be within the scope defined by the claims of the present invention.
Claims
1. A regenerable hydrogenation catalyst, characterized in that The catalyst uses SiO2-TiO2 composite as carrier, palladium and rhodium as active components, and additives are added. The catalyst composition is as follows: PdRh-M / MP(m)-SiO2 / TiO2(n) Wherein, the content of loaded palladium is 1-5wt%, and the content of loaded rhodium is 0.5-3wt%; Wherein, M is a catalyst additive, MP is an additive phosphide, and the content of the two additives is 1-10wt%; Wherein, MP partially phosphatizes M, and preferably the molar ratio m of the auxiliary agent M to MP is 5-20.
2. A method for preparing the catalyst according to claim 1, characterized in that: The method comprises the following steps: S1: A mixed solution of silicon source and titanium source is prepared and then aged, washed, dried and calcined to obtain a SiO2-TiO2 composite carrier; S2: Grind the carrier into powder, add the precursor salt solution of M, mix, and dry to obtain the intermediate A with added M; S3: Partially phosphating the intermediate A to obtain the intermediate B; S4: Grind the intermediate B into powder, add solutions of palladium salt and rhodium salt, mix, dry and reduce to obtain the target catalyst; Optionally, S5: the used catalyst is dried and partially phosphated again to obtain a regenerated catalyst.
3. The method according to claim 2, characterized in that S1 The silicon source comprises a silicate compound, preferably one or more of ethyl orthosilicate, methyl orthosilicate, and tetrabutyl silicate; And / or, the titanium source in S1 comprises alkyl titanate, preferably tetrabutyl titanate and / or tetrapropyl titanate; Preferably, the molar ratio n of silicon to titanium atoms is 8-15; Preferably, the m / n ratio is 2:1-1:2; and / or, adding a surfactant to S1, preferably the surfactant is a nonionic surfactant, more preferably one or more of F127, F108 and P123; and / or, adding an acid to S1, preferably the acid is an inorganic acid, more preferably hydrochloric acid; Preferably, the mass ratio of surfactant to acid is 1:(1.2-1.8); and / or, the aging treatment time in S1 is 24-72h and the temperature is 150-220°C; And / or, the calcination temperature in S1 is 400-650° C. and the time is 4-8 h.
4. The method according to claim 2, characterized in that: The precursor salt of M in S2 comprises a soluble salt of one or more of Fe, Co, Zn, and Ni, preferably one or more of iron nitrate, cobalt nitrate, zinc nitrate, and nickel nitrate.
5. The method according to claim 2, characterized in that: The phosphating agent used in the S3 phosphating treatment comprises an inorganic phosphate, preferably one or more of sodium phosphate, sodium hydrogen phosphate, and sodium dihydrogen phosphate; And / or, the phosphating temperature in S3 is 200-500°C and the time is 1-3h.
6. The method according to claim 2, characterized in that The palladium salt in S4 comprises one or more of chloroplatinic acid, platinum nitrate, platinum tetrachloride, and potassium chloroplatinate; And / or, the rhodium salt in S4 comprises rhodium nitrate and / or rhodium trichloride; And / or, S4 is reduced to a hydrogen atmosphere at a temperature of 200-400° C. for 2-4 h.
7. The method according to claim 2, characterized in that The phosphating method in S5 is the same as that in S3.
8. Use of a regenerable hydrogenation catalyst, wherein the catalyst is the catalyst according to claim 1, or a catalyst prepared by the method according to any one of claims 2 to 7, and the catalyst is used for hydrogenation reaction, preferably for nitrobenzene hydrogenation.
9. A method for hydrogenating nitrobenzene using a renewable hydrogenation catalyst, the method using the catalyst of claim 1, or a catalyst prepared by the method of any one of claims 2 to 7, characterized in that: In the method, the reaction temperature is 80-200° C., the reaction pressure is 0.5-2 MPaG, and the molar ratio of hydrogen to nitrobenzene is (3-3.5):1.
Citation Information
Patent Citations
Nitrobenzene hydrogenation catalyst and preparation method thereof
CN114632512A